The Use of Simultaneous Equation Model (SEM) in Understanding the Dynamic Relationships Between Economic Openness and Real Disposable Personal Income on Inflation: the Indonesian Experience - Huda, Fahmi Alamil (Muslim Business and Economics Review, 2022)
This paper examines the relationship between the degree of economic openness and real disposable personal income on inflation in Indonesia for a twenty-one-year period (2000Q1–2021Q3). The Simultaneous Equation Model (SEM) technique and the TSLS–Two Stage Least Squares (TSNLS and ARMA) method and long-term dependence for quarterly data from March 2001 (2001Q1) to September 2021 (2021Q3) were used to analyse and test the data. The study shows that the variables degree of openness of the economy (lopen) and real disposable personal income (ldpi) had a significant effect on inflation (linf) with a significance level of 5%. Interestingly, the estimates tend to show an appropriate sign and magnitude of the economic coefficient significance. The study has some implications. It explains the openness of the Indonesian economy and the real disposable personal income of the Indonesian population to recent inflation. Additionally, choosing appropriate policy actions to increase the competitiveness of Indonesia's export products both competitively and comparatively are discussed. If the permanent disposable income of people in Indonesia increases, the consumption demand for certain goods and services will also increase. When the demand for an item is high, the raw materials to be used also become scarce and this can cause inflation. In the context of fiscal stabilization, the Government is expected to be able to provide permanent non-cash subsidies that can help people generate permanent income independently and sustainably so that it has an impact on smoothing their consumption path over time.